2020
DOI: 10.1038/s41559-020-01366-z
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: Conservative route to genome compaction in a miniature annelid

Abstract: A Correction to this paper has been published: https://doi.org/10.1038/s41559-020-01327-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…The genomic consequences of miniaturization are poorly understood given the dearth of genomes from microscopic animals. Work to date has revealed that while some small-bodied lineages exhibit drastic simplification of genome architecture and reduction in content with respect to their large-bodied relatives (Seo et al 2001; Mikhailov et al 2016), have taken a more conservative route in regards to genome compaction (Martín-Durán et al 2021; reviewed by Worsaae et al 2023). Increased genomic sampling broadly spanning the metazoan tree stands to provide insight into genomic signatures of miniaturization.…”
Section: Discussionmentioning
confidence: 99%
“…The genomic consequences of miniaturization are poorly understood given the dearth of genomes from microscopic animals. Work to date has revealed that while some small-bodied lineages exhibit drastic simplification of genome architecture and reduction in content with respect to their large-bodied relatives (Seo et al 2001; Mikhailov et al 2016), have taken a more conservative route in regards to genome compaction (Martín-Durán et al 2021; reviewed by Worsaae et al 2023). Increased genomic sampling broadly spanning the metazoan tree stands to provide insight into genomic signatures of miniaturization.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, also in this respect, the new sequencing technologies brought substantial progress. Nowadays, it is possible to sequence high‐quality genomes for different plants, fungi, protists and animals including non‐model species and species with very large and complex genomes, with very small body sizes, with high ploidy levels or with low‐quality preservation status (Cerca et al, 2022; Kingan et al, 2019; Kwiatkowski et al, 2021; Martín‐Durán et al, 2020; Meyer et al, 2021; Schloissnig et al, 2021; Schneider et al, 2021; Varney et al, 2022). This has led to the proposal of a biological moonshot mission, the sequencing of a reference genome for each known eukaryotic species on Earth (Lewin et al, 2018).…”
Section: Understanding Biodiversity Change ‐ the Potential Of Combini...mentioning
confidence: 99%
“…Studies on these topics focusing on meiofauna arecomparatively limited and lag behind compared to those on large-bodied animals (Miller et al, 2022). Despite that, recent collaborative efforts among phylogenetists, morphologists, and systematists have significantly enhanced our capacity to integrate morphological and genomic data (Fonseca et al, 2017;Smythe et al, 2019;Martín-Durán et al, 2021;Herranz et al, 2022).…”
Section: Panel III Morphology and Adaptationmentioning
confidence: 99%
“…Genomic tools will be essential to understand the evolutionary processes and biological mechanisms responsible for biotic and abiotic adaptations in meiofauna. The analysis of genomic data will also be paramount in calculating the speed of evolutionary change and the history of morphologically cryptic species complexes (Q#88) (Bickford et al, 2007;Felix et al, 2014;Cerca et al, 2021) (see Panel I); but also, to understand the genetic basis for adaptation (Savolainen et al, 2013;Martín-Durán et al, 2021). Hand-in-hand with cryptic species inference using population genomic approaches is the interrogation of gene flow among populations and incipient species (i.e., hybrid introgression) and the drivers of its restrictions (Q#85).…”
Section: Panel IV Genome Biology and Evolutionmentioning
confidence: 99%
See 1 more Smart Citation